Effects of Tendon Gliding Exercises on the Speed of Handwriting Among Female UG Students: Pilot Study - Abhishruti Das; Larbin Teronpi; Prasenjit Bhattacharyya; Santosh Kumar Rajak (International Journal of Evidence Based Nursing And Practices, 2025)
Background: Handwriting is an intricate function which requires the combination of fine motor skills, visual and motor coordination abilities, and concentration. Handwriting involves two main movements: horizontal wrist motion and vertical finger movements, along with a rightward translation of the entire arm. Handwriting speed is an important factor in a student’s academic performance, particularly in fields such as statistics. The strength and flexibility of hand muscles can significantly influence writing speed. Tendon gliding exercises are considered an effective method for improving finger movement and strength, which may directly impact handwriting speed. Objective: The aim of this study was to assess the effect of tendon gliding exercises on handwriting speed among undergraduate physiotherapy students. Methodology: An experimental study was conducted with 30 female students aged 18 to 23 years. The participants were randomly selected and evaluated based on specific inclusion and exclusion criteria. Handwriting speed was measured using a "words per minute" test for 3 min, following the guidelines of Wallen et al. Tendon gliding exercises were demonstrated to the participants, who were instructed to perform them unsupervised for 4 days a week over a 4-week period. The outcome was reassessed after 4 weeks using the same measurement tool. Results: All 30 female students completed the study. After 4 weeks, a comparison was made between pre-test and post-test results. The mean value before the intervention was 72.97, while after the intervention, it increased to 77.03. A statistically significant difference was found between the pre-test and post-test scores, with a p-value of 0.0001. Conclusion: The study demonstrated a significant improvement in handwriting speed after performing tendon gliding exercises, as evidenced by the statistical analysis of pre-test and post-test results. So, as a result, tendon gliding exercises showed beneficial effects on improving the handwriting speed of the undergraduate students.
Keywords: Tendon gliding exercise; speed of handwriting; undergraduate female students